Mercury photoreduction and photooxidation kinetics in estuarine water: Effects of salinity and dissolved organic matter. (January 2023) - Clarke, Rachel G.; Klapstein, Sara J.; Keenan, Robert; O'Driscoll, Nelson J.
Abstract: Net photoreduction of divalent mercury (Hg(II)) and volatilization of photoreduction products (i.e., elemental mercury (Hg(0))/dissolved gaseous mercury (DGM)) is a mechanism by which mercury burdens in ecosystems are lessened. The effects of salinity on mercury photoreactions were investigated while controlling the concentration of DOM (>1 kDa) using natural surface water from the tidal Jijuktu'kwejk (Cornwallis River) and processed with a tangential ultrafiltration-dilution technique. Pseudo first-order rate constants in estuarine water salinity dilutions ranged between 0.22 h −1 and 0.73 h −1 . The amount of mercury available for photoreduction (Hg(II)RED ) ranged between 67.2 and 265.9 pg. Pseudo first-order rate constants decreased with increasing salinity treatments (0–13.5 g L −1 ), with minimal change in rate constants occurring in higher salinity treatments (e.g. 20.3 or 26.8 g L −1 ), while Hg(II)RED increased with salinity. In lower salinity treatments, DOM was more photoactive. Taken together, results suggest changes in the mercury photoreduction mechanism from DOM-bound electron transfer to photochemically produced secondary reduction products with increasing salinity. Experiments examining photooxidation showed decreases in Hg (0) with longer exposure time, suggesting transformation of Hg(II)RED into a non-reducible form. This research highlights the importance of salinity and DOM interactions in estuarine surface water and their effects on mercury photochemistry. Graphical abstract: Image 1 Highlights: Photoreduction of divalent mercury (Hg(II)) and can lessen both mercury concentrations and methylation potential in ecosystems. Photoreduction rates ranged between 0.22 h −1 and 0.73 h −1 and photoreducible mercury (Hg(II)RED ) between 67.2 and 265.9 pg. Photoreduction rates decreased with increasing salinity (0–13.5 g L −1 ), with minimal change at higher salinities, while Hg(II)RED increased with salinity. Abstract : The influence of salinity on mercury photoreactions in estuaries is not well studied. This study reports interactions between salinity and DOM, potentially inhibiting Hg(II) photoreduction in estuaries.